Leaving : a narrative of assisted suicide - Stavrianakis, Anthony (University of California Press, 2019)
"The first book-length anthropological study of voluntary assisted dying, Leaving is a narrative account of five case histories of people who ended their lives with assistance in Switzerland. Anthony Stavrianakis places his narrative within a larger story about how to approach and understand the practice of assisted suicide, one that is often integrated into moral positions that reflect sociological and psychological commonplaces about both suicide and euthanasia. Leaving argues that such commonplaces are wildly inappropriate and cannot encompass the larger experiences of those who seek this specific form through which to leave their experience of life and illness"--